Equity research - Nike, inc - Marques, Nuno Miguel Rocha (2021)
Conducted between November 2021 and December 2021, the objective of this equity analysis was to determine the intrinsic value of NIKE, Inc. to recommend an investment decision. Utilizing quantitative and qualitative information, financial forecasts of NIKE, Inc.’s key metrics and performance were made. Upon completion of the forecasts, a Discounted Cash-Flow model was applied to reach a target price. The report concludes that NIKE, Inc.’s business outlook is favorable, thus resulting in a buy recommendation, with a target share price of $202.63.